SIMULASI SISTEM KEAMANAN TERPADU PADA KOMPLEK PERUMAHAN MENGGUNAKAN SENSOR INFRAMERAH - Adenia Kahfianti; Nurwijayanti Kusumaningrum (JURNAL TEKNOLOGI INDUSTRI, 2019)
The basic need that humans need is a place to live. A place to live with a good environment and good security is a dream place for everyone. The security system is made using the Arduino Uno microcontroller as a controller of the system, an infrared sensor as a detector and a GSM module that will notify the home owner. When the infrared sensor detects an obstacle, the LED and Buzzer at the security post will sound and will not stop until the security guard knows and turns off the LED and Buzzer. In the event of a robbery, the owner of the house will be notified via SMS (Short Message Service).Keywords: Housing Security System, Integrated security system, GSM 800L Module, Infrared Sensor